The men who gave us wings Britain and the aeroplane 1796-1914 - Reese, Peter 1932- (Pen & Sword Military, 2014)
Why did the British, then the leading nation in science and technology, fall far behind in the race to develop the aeroplane before the First World War? Despite their initial advantage, they were overtaken by the Wright brothers in America, by the French and the Germans. Peter Reese, in this highly readable and highly illustrated account, delves into the fascinating early history of aviation as he describes what happened and why. He recalls the brilliant theoretical work of Sir George Cayley, the inventions of other pioneers of the nineteenth century and the daring exploits of the next generation of airmen, among them Samuel Cody, A.V. Roe, Bertram Dickson, Charles Rolls and Tommy Sopwith. His narrative is illustrated with a wonderful selection of over 120 archive drawings and photographs which record the men and the primitive flying machines of a century ago.